A cross‐practice context exploration of nursing preparedness and comfort to care for people with intellectual disability and autism. Issue 19 (16th November 2021) - Cashin, Andrew; Pracilio, Amy; Buckley, Thomas; Morphet, Julia; Kersten, Michelle; Trollor, Julian N.; Griffin, Ken; Bryce, Julianne; Wilson, Nathan J.
Abstract: Aims and Objectives: To compare the self‐perceived preparedness, knowledge, comfort and confidence of Australian Registered Nurses when caring for people with ID and/or ASD across contexts of practice: primary care and community, intensive care, acute hospital, emergency department, paediatrics and ID/ASD. Background: There is limited research comparing nursing preparedness and competency when caring for people with intellectual disability (ID) and/or autism (ASD) across nursing contexts of practice. A greater understanding of the differed educational preparedness, confidence and comfort across contexts of practice can aid the development of tailored educational programmes to improve nursing capacity to care for this cohort. Design: Cross‐sectional descriptive study. Methods: A descriptive survey tool of registered nurses ( n  = 69.3). Comparative inferential analysis was undertaken between the independent categorical variable of six nursing contexts of practice across several dependent variables including age, years since registration, educational content and exposure, knowledge, comfort and confidence. This cross‐sectional study was undertaken according to the STROBE Statement checklist of items. Results: Occupying an ID/ASD nursing role was significantly associated with higher reported levels of educational preparedness, professional development and postgraduate education relevant to caring for people with ID and/or ASD. Levels of self‐reported knowledge of care issues, confidence and comfort when undertaking healthcare tasks was significantly associated with the context of practice, with nurses working in ID/ASD settings reporting the highest levels across all variables. Conclusion: The findings of the study highlight an association between greater educational exposure to content relevant to working with people with ID/ASD and subsequently working in that field. Relevance to clinical practice: This study has highlighted that professional development programmes aiming to improve nursing capacity to care for people with ID and/or ASD, should be informed by and address differing gaps in confidence, comfort and educational preparedness across nursing contexts of practice.